2021
DOI: 10.1093/jee/toaa314
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Susceptibility of Thrips palmi to Spinetoram and Frequency of G275E Mutation Provides Basis for Molecular Quantification of Field-Evolved Resistance

Abstract: Putative mechanisms underlying spinosyn resistance have been identified in controlled studies on many species; however, mechanisms underlying field-evolved resistance and the development of a molecular diagnostic method for monitoring field resistance have lagged behind. Here, we examined levels of resistance of melon thrips, Thrips palmi Karny (Thysanoptera:Thripidae), to spinetoram as well as target site mutations in field populations across China to identify potential mechanisms and useful molecular markers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 8 publications
(22 citation statements)
references
References 38 publications
0
22
0
Order By: Relevance
“…We compared the toxicity of broflanilide to T. palmi with that of five other insecticides. Spinosyns are the most frequently used insecticides in controlling thrips pests, 4,10,12 but field populations of thrips have developed resistance to the spinosyns in many areas 10,22,34 . In the two populations of T. palmi tested, one population had an LC 50 of 0.3385 while the other had a much higher value >47 mg L −1 , indicating the reduced susceptibility of this population to spinetoram.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We compared the toxicity of broflanilide to T. palmi with that of five other insecticides. Spinosyns are the most frequently used insecticides in controlling thrips pests, 4,10,12 but field populations of thrips have developed resistance to the spinosyns in many areas 10,22,34 . In the two populations of T. palmi tested, one population had an LC 50 of 0.3385 while the other had a much higher value >47 mg L −1 , indicating the reduced susceptibility of this population to spinetoram.…”
Section: Discussionmentioning
confidence: 99%
“…Spinosyns are the most frequently used insecticides in controlling thrips pests, 4,10,12 but field populations of thrips have developed resistance to the spinosyns in many areas. 10,22,34 In the two populations of T. palmi tested, one population had an LC 50 of 0.3385 while the other had a much higher value >47 mg L −1 , indicating the reduced susceptibility of this population to spinetoram. However, previous studies showed that the baseline susceptibility of spinosyns in this thrips species is only about 0.1 mg L −1 .…”
Section: Toxicity Of Broflanilide To Thrips Pests Compared To Other P...mentioning
confidence: 98%
See 1 more Smart Citation
“…The resistance level of field populations of Thrips palmi to spinetoram is linearly related to the frequency of the G275E mutation. 17 This system provides an ideal model to test not only the utility of KASP for genotyping the resistance locus but also for testing whether the method can be used to semi-quantify mutation frequency at the population level. Our study highlights the usefulness of this method in both contexts.…”
Section: Introductionmentioning
confidence: 99%
“…The susceptibility of each population to spinetoram was tested using the bioassay method in the laboratory, and the G275E mutation was examined by PCR amplification and Sanger sequencing of target DNA, including this site. The resistance level of field populations of Thrips palmi to spinetoram is linearly related to the frequency of the G275E mutation 17 . This system provides an ideal model to test not only the utility of KASP for genotyping the resistance locus but also for testing whether the method can be used to semi‐quantify mutation frequency at the population level.…”
Section: Introductionmentioning
confidence: 99%